1988
DOI: 10.1007/bf01746679
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of Tamm—Horsfall protein in human kidney using immunogold electron microscopy

Abstract: The ultrastructural localization of Tamm-Horsfall protein (THP) was studied in paraformaldehyde-fixed human renal biopsies. Pre-embedding and post-embedding immunogold labelling techniques were developed utilizing a monoclonal antibody specific for human urinary THP. With the pre-embedding technique, membrane contrast was enhanced by osmification thus allowing precise localization of gold particles. Reasonable tissue penetration of antibodies was achieved without compromising ultrastructural detail. The hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…Similar variability in storage has been described before (Gubler et al 1978). As in previous studies on UMOD expression in control kidney, we observed prominent expression of UMOD in the TALH and less so in the DCT in normal kidneys (Hoyer and Seiler 1979;Peach et al 1988;Schenk et al 1971;Sikri et al 1981). Thus, both processes, lysosomal storage and UMOD expression, meet in the TALH.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar variability in storage has been described before (Gubler et al 1978). As in previous studies on UMOD expression in control kidney, we observed prominent expression of UMOD in the TALH and less so in the DCT in normal kidneys (Hoyer and Seiler 1979;Peach et al 1988;Schenk et al 1971;Sikri et al 1981). Thus, both processes, lysosomal storage and UMOD expression, meet in the TALH.…”
Section: Discussionsupporting
confidence: 89%
“…Abbreviations DCT distal convoluted tubule ERT enzyme replacement therapy Gb 3 globotriaosylceramide GLA !-galactosidase A MALDI-TOF matrix assisted lased desorption/ ionization-time of flight SRT substrate reduction therapy TALH thick ascending limb of Henle_s loop UAKD uromodulin-associated kidney disease UMOD uromodulin thick ascending limb of Henle_s loop (TALH), the macula densa segment and the distal convoluted tubule (DCT) (Hoyer and Seiler 1979;Peach et al 1988;Schenk et al 1971;Sikri et al 1981). Normally the synthesized protein is glycosylated, glypiated, secreted and glycosylphosphatidylinositol-anchored in the apical membrane of the polarized renal tubular epithelial cells (Kreft et al 2002;Rindler et al 1990;Serafini-Cessi et al 1993), from where it is continuously released by a specific but not yet identified protease (Cavallone et al 2001;Fukuoka and Kobayashi 2001).…”
mentioning
confidence: 99%
“…We conclude that TAL affects the susceptibility of S3 segments to injury at least in part by regulating MIP-2 expression in a THP-dependent manner. Our findings raise the interesting possibility of a direct role of basolaterally released THP on regulating inflammation in S3 segments.CXCL2; ischemia-reperfusion; uromodulin; acute kidney injury TAMM-HORSFALL PROTEIN (THP) is a unique glycoprotein because it is exclusively expressed in the kidney, specifically in thick ascending limbs (TALs) and early distal tubules (4,15,29). Although this glycoprotein was discovered 60 years ago (37), its functions are still not fully understood (35).…”
mentioning
confidence: 99%
“…CXCL2; ischemia-reperfusion; uromodulin; acute kidney injury TAMM-HORSFALL PROTEIN (THP) is a unique glycoprotein because it is exclusively expressed in the kidney, specifically in thick ascending limbs (TALs) and early distal tubules (4,15,29). Although this glycoprotein was discovered 60 years ago (37), its functions are still not fully understood (35).…”
mentioning
confidence: 99%
“…Within the kidney, THP has been localized by immunohistochemistry and in situ hybridization to the thick ascending limb of Henle's loop (TALH) and the early distal convoluted tubules (2,3,17,27,40). At these locations, THP is believed to be membrane-anchored via its COOH-terminal glycophosphatidylinositol linkage, but the protein can be released into the urine by the action of phospholipases or proteases (7,9,15,28,34).…”
mentioning
confidence: 99%